ChemInform Abstract: One‐Pot Synthesis of a 1, 2‐Diphospholide by Double C—H Deprotonation. Issue 28 (July 2015) - Dixon, Lily S. H.; Matthews, Peter D.; Solomon, Sophia A.; Wright, Dominic S.
Abstract A new high‐yielding and direct route to the 1, 2‐diphospholide ligand framework using a very simple approach is presented.